Selection for Technology Acquisition using AHP: A Case Study of Tulip VAWT Effectiveness - Baskoro, Gembong; Sarwono, Edhie; Subekti, Galih Akup; Hendriana, Dena; Nasution , Henry (Jurnal Teknik Industri, 2024)
The increasing energy demand in Indonesia, particularly from the industrial sector, has heightened the need to reduce reliance on fossil fuels by integrating new and renewable energy (NRE) sources into the energy mix. For the industrial sector, adopting NRE technologies presents options such as purchasing, manufacturing, or acquiring technology. This study focuses on selecting the most effective option for a small Vertical Axis Wind Turbine (VAWT), specifically the Tulip VAWT, by evaluating its hardware performance. The selection process utilizes subjective judgment and the Analytical Hierarchy Process (AHP), considering five key factors: installability, usability, affordability, availability, and maintainability. Results indicate that Technology Acquisition (TA) is the optimal choice, with an AHP score of 0.65, outperforming the purchasing options (0.322) and manufacturing options (0.296). These findings suggest that evaluating these five factors significantly impacts the decision-making process regarding adopting the Tulip VAWT. However, the study does not assess the effectiveness of the associated knowledge (software) or organizational factors, as no established methodology exists for this evaluation yet.